Conservation of vaccine antigen sequences encoded by sequenced strains of Streptococcus equi subsp. equi. (19th January 2022) - Frosth, Sara; Morris, Ellen Ruth A.; Wilson, Hayley; Frykberg, Lars; Jacobsson, Karin; Parkhill, Julian; Flock, Jan‐Ingmar; Wood, Tim; Guss, Bengt; Aanensen, David M.; Boyle, Ashley G.; Riihimäki, Miia; et al.
Summary: Background: Streptococcus equi subspecies equi ( S equi ) is the cause of Strangles, one of the most prevalent diseases of horses worldwide. Variation within the immunodominant SeM protein has been documented, but a new eight‐component fusion protein vaccine, Strangvac, does not contain live S equi or SeM and conservation of the antigens it contains have not been reported. Objective: To define the diversity of the eight Strangvac antigens across a diverse S equi population. Study design: Genomic description. Methods: Antigen sequences from the genomes of 759 S equi isolates from 19 countries, recovered between 1955 and 2018, were analysed. Predicted amino acid sequences in the antigen fragments of SEQ0256(Eq5), SEQ0402(Eq8), SEQ0721(EAG), SEQ0855(SclF), SEQ0935(CNE), SEQ0999(IdeE), SEQ1817(SclI) and SEQ2101(SclC) in Strangvac and SeM were extracted from the 759 assembled genomes and compared. Results: The predicted amino acid sequences of SclC, SclI and IdeE were identical across all 759 genomes. CNE was truncated in the genome of five (0.7%) isolates. SclF was absent from one genome and another encoded a single amino acid substitution. EAG was truncated in two genomes. Eq5 was truncated in four genomes and 123 genomes encoded a single amino acid substitution. Eq8 was truncated in three genomes, one genome encoded four amino acid substitutions and 398 genomes encoded a single amino acid substitution at the final amino acid of the Eq8 antigen fragment. Therefore, at least 1579 (99.9%) of 1580 amino acids in Strangvac were identical in 743 (97.9%) genomes, and all genomes encoded identical amino acid sequences for at least six of the eight Strangvac antigens. Main limitations: Three hundred and seven (40.4%) isolates in this study were recovered from horses in the UK. Conclusions: The predicted amino acid sequences of antigens in Strangvac were highly conserved across this collection of S equi .